The application of ultrasound at high temperature - Jamaludin, Khairur Rijal (Universiti Teknologi Malaysia, 2002)
Ultrasound becomes more relevant in today's industries. This is due to its wide range of application and ability to perform testing without destructing the sample and, without shutting down the plant operation. This paper presents several ultrasound techniques that are suitable for high temperature measurements